Differences in Clinical Pain and Experimental Pain Sensitivity Between Asian Americans and Whites With Knee Osteoarthritis. Issue 2 (February 2017) - Ahn, Hyochol; Weaver, Michael; Lyon, Debra E.; Kim, Junglyun; Choi, Eunyoung; Staud, Roland; Fillingim, Roger B.
Abstract : Objective: Ethnicity has been associated with clinical and experimental pain responses. Whereas ethnic disparities in pain in other minority groups compared with whites are well described, pain in Asian Americans remains poorly understood. The purpose of this study was to characterize differences in clinical pain intensity and experimental pain sensitivity among older Asian American and non-Hispanic white (NHW) participants with knee osteoarthritis (OA). Methods: Data were collected from 50 Asian Americans ages 45 to 85 (28 Korean, 9 Chinese, 7 Japanese, 5 Filipino, and 1 Indian) and compared with 50 age-matched and sex-matched NHW individuals with symptomatic knee OA pain. The Western Ontario and McMaster Universities Osteoarthritis Index and Graded Chronic Pain Scale were used to assess the intensity of clinical knee pain. In addition, quantitative sensory testing was used to measure experimental sensitivity to heat-induced and mechanically induced pain. Results: Asian American participants had significantly higher levels of clinical pain intensity than NHW participants with knee OA. In addition, Asian American participants had significantly higher experimental pain sensitivity than NHW participants with knee OA. Discussion: These findings add to the growing literature regarding ethnic and racial differences in clinical pain intensity and experimental pain sensitivity. Asian Americans in particular may be at risk for clinical pain and heightened experimental pain sensitivity. Further investigation is needed to identify the mechanisms underlying ethnic group differences in pain between Asian Americans and NHWs, and to ensure that ethnic group disparities in pain are ameliorated.